Acellular Dermal Matrix–Associated Contracture: A Clinical and Histologic Analysis of Patients Undergoing Prosthetic Breast Reconstruction. (8th September 2021) - Kearney, Aaron M.; Yan, Yufan; Bricker, Jonathan T.; Pincus, Jennifer L.; Alghoul, Mohammed S.
Abstract : Background: Capsular contracture is a well-recognized complication following prosthetic breast reconstruction. It has been the authors' observation that some patients undergoing breast reconstruction experience contracture specifically of the acellular dermal matrix placed at the time of their tissue expander insertion. The goal of the authors' study was to identify clinical and histologic findings associated with the development of acellular dermal matrix–associated contracture. Methods: The authors performed a retrospective cohort study of all patients undergoing bilateral implant-based breast reconstruction performed by the senior author (M.S.A.). Patients were excluded if they had radiation therapy to the breast. Patients with suspected acellular dermal matrix–associated contracture were identified by clinical photographs and review of operative notes. Histologic analysis was performed on specimens taken from two patients with acellular dermal matrix contracture. Results: The authors included a total of 46 patients (92 breasts), of which 19 breasts had suspected acellular dermal matrix–associated contracture. Acellular dermal matrix contracture was less common in direct-to-implant reconstruction (4.2 percent versus 26.5 percent; p = 0.020) and more common in breasts that had seromas (0 percent versus 15.8 percent; p = 0.001) or complications requiring early expander replacement. Contracted acellular dermal matrix had less vascularity and a lower collagen I–to–collagen III ratio, and was twice as thick as noncontracted acellular dermal matrix. Conclusions: The authors have described a distinct phenomenon of acellular dermal matrix–associated contracture that occurs in a small subset of breasts where acellular dermal matrix is used. This merits further investigation. Future work will be required to better characterize the clinical factors that make acellular dermal matrix–associated contracture more likely to occur. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.